The development of genially-based interactive learning multimedia for elementary school students - Putra, Lovandri Dwanda; Afrina, Nuryah (Universitas Ahmad Dahlan, 2023)
This research focuses on producing genially-based interactive multimedia learning for fifth-grade elementary/MI students. This research belongs to the type of research and development research and development (RND). The procedure for developing genially-based interactive learning multimedia uses a development model developed by Sugiyono with ten stages, namely potential and problems, data collection, product design, design validation, product revision, initial trial, product revision, usage trial, product revision, and mass production. However, in the current state of the COVID-19 pandemic and the limited time, conditions, and costs, researchers only carried out these stages, only to stage 9, namely product revision. The results of the validation by media experts with a score of 71 in the good category, material experts with a score of 86.6 in the very good category, and learning experts with a score of 80 in the very good category, so that genially-based interactive learning multimedia is feasible to use. The results of the responses of the SD Muhammadiyah Karangkajen II class teachers in the initial trial, namely by obtaining a score of 82.2 with a very good category, then the results of the responses of the students of SD Muhammadiyah Karangkajen II in the initial trial with the subject of 4 students with a score of 90 in the very good category, while the response of students in the use trial with the subject of 19 students with a score of 95.2 with a very good category. Then, the average value of student responses is 92.6. Based on the results of teacher and student responses, genially based interactive multimedia learning is feasible to use.